Internalising Environmental Values through Islamic Religious Education in Junior High School: Internalisasi Nilai-Nilai Lingkungan Hidup melalui Pendidikan Agama Islam di Sekolah Menengah Pertama - Serly, Ayunda; Khozin, Khozin; Hakim, Rahmad (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the process of internalizing environmental character values through Islamic Religious Education (IRE) at SMP Alam Insan Mulia Lubuklinggau. Employing a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation involving the principal, vice principal for curriculum, and Islamic studies teachers. Data were analyzed using Miles and Huberman’s interactive model. The findings reveal that the internalization process follows three stages: value transformation, value transaction, and transinternalization, aligned with Thomas Lickona’s character components moral knowing, moral feeling, and moral action. The theoretical novelty of this study lies in integrating Lickona’s framework with Islamic values in the unique context of a nature-based Islamic school, which remains underexplored in existing literature. Practically, the findings offer insights for teachers and principals to design contextual IRE learning and for policymakers to promote Islamic-based environmental education. This study is limited to a single school context, hence its findings are not broadly generalizable; future research should involve diverse educational settings to enrich theoretical and practical perspectives. Highlights: Three-Stage Process: Internalization is done through transformation, transaction, and transinternalization stages. Lickona’s Integration: Combines moral knowing, feeling, and action with Islamic values. Contextual Insight: Offers a unique case from a nature-based Islamic school, informing IRE teaching practice and policy. Keywords: Value Internalization, Environmental Character, Islamic Education, Nature-Based School